Two novel trimethylsulfonium salts with polymeric {[SbCl4]−}n or {[CdCl3]−}n anions. Issue 2 (10th January 2014) - Liu, Ming‐Liang; Kong, Li‐Hui
<x xml:space="preserve">Abstract</x> The title organic–inorganic hybrid salts poly[trimethylsulfonium [[dichloridoantimony(III)]‐di‐μ‐chlorido]], {(C3H9S)[SbCl4]}n, (I), and catena‐poly[trimethylsulfonium [cadmium(II)‐tri‐μ‐chlorido]], {(C3H9S)[CdCl3]}n, (II), consist of trimethylsulfonium cations and polymeric {[SbCl4]−}n or {[CdCl3]−}n anions. The central metal atoms are coordinated by six Cl atoms, forming an anionic {[SbCl4]−}n three‐dimensional framework (two of the four bridging chloride anions are located on two different centres of inversion) or anionic {[CdCl3]−}n one‐dimensional chains. The trimethylsulfonium cation of (II) is disordered over two sets of sites in a 0.791 (4):0.209 (4) ratio. All the anions are linked by trimethylsulfonium cations through weak C—H...Cl hydrogen bonds to form three‐dimensional structures.